Моя неугомонная ведьма - Орам Гиавин (Дневник кота Баламута, 2009)
Экземпляры: СФ-2 (20100914) / Инвентарный номер: 39089z2 / Цена: 167.80 / Сис.шифр: 84(4Вел) / Авт.знак: О-63 / ГРНТИ: 17.82 / ББК: 84(4Вел)